Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1097/mao.0000000000003618
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Preservation After Intervention in Vestibular Schwannoma

Abstract: ObjectiveThis study aimed to assess the durability of audiological outcomes after radiation and surgery in the management of vestibular schwannoma.Study DesignRetrospective review.SettingTertiary academic center.PatientsAdults with sporadic vestibular schwannoma and serviceable hearing at the time of intervention.InterventionsGamma Knife, middle cranial fossa, or retrosigmoid approaches.Main Outcome MeasuresPure-tone audiometry and speech discrimination scores.ResultsPostintervention serviceable hearing (class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
(106 reference statements)
0
5
0
1
Order By: Relevance
“…Other authors found that serviceable hearing (Class A/B) was preserved in 70.4% of patients [15 ]. Unfortunately, this preservation of acoustic function could deteriorate with time [16,17].In our group of patients, 55 (91%)…”
Section: Discussionmentioning
confidence: 56%
“…Other authors found that serviceable hearing (Class A/B) was preserved in 70.4% of patients [15 ]. Unfortunately, this preservation of acoustic function could deteriorate with time [16,17].In our group of patients, 55 (91%)…”
Section: Discussionmentioning
confidence: 56%
“…Further loss in the contralateral ear (e.g., presbycusis) of PTA or WRS could be applied to the treated ear diminishing the effect attributed to radiation. A formula for this calculation provides for this adjustment 49 . However, due to obtaining frequent post‐treatment audiograms only the involved ear was tested and the contralateral ear was not routinely monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Yancey et al reviewed their experience with surgery and radiation for VS. 49 At 5 years their estimate for maintaining serviceable hearing (AAO-HNS class A/B) was 28%. Their 10-year Kaplan Meier estimates for preserving serviceable hearing dropped to 14.2%.…”
Section: Hearing Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…Mehrere Studien zeigten, dass die SRS bei VS von weniger als 3cm im Hinblick auf die Erhaltung des Gesichtsnervs und der Hörfunktion wirksamer ist als die Mikrochirurgie [68,70,72,73,74,75]. Yancey et al beschreiben keinen signifikanten Unterschied des Hörerhalts nach Resektion oder Gamma-Knife-Behandlung bei Erwachsenen mit ausreichender Hörfunktion bei Diagnose [76]. Eine SRS vor Mikrochirurgie geht mit einer erhöhten Morbidität und insbesondere häufigeren Fazialislähmungen einher [77].…”
Section: Bestrahlungunclassified